Calculating the home advantage in soccer leagues - Gómez, M.-A.; Pollard, R. (Journal of Human Kinetics, 2014)
A recent article published in the Journal of Human Kinetics (Saavedra et al., 2013) was based on a flawed methodology when calculating the home advantage values in soccer leagues. This led to incorrect calculations, false conclusions and some misleading results about home advantage in 52 soccer leagues of UEFA countries over a 10 year period. The aim of this letter was to explain these flaws and to make sure future research would not be influenced by the subsequent results and conclusions that had been presented